The impact of exercise on mitochondrial dynamics and the role of Drp1 in exercise performance and training adaptations in skeletal muscle - Timothy M. Moore; Zhenqi Zhou; Whitaker Cohn; Frode Norheim; Amanda J. Lin; Nareg Kalajian; Alexander R. Strumwasser; Kevin Cory; Kate Whitney; Theodore Ho; Timothy Ho; Joseph L. Lee; et al. (Elsevier, 2019)
Objective: Mitochondria are organelles primarily responsible for energy production, and recent evidence indicates that alterations in size, shape, location, and quantity occur in response to fluctuations in energy supply and demand. We tested the impact of acute and chronic exercise on mitochondrial dynamics signaling and determined the impact of the mitochondrial fission regulator Dynamin related protein (Drp)1 on exercise performance and muscle adaptations to training. Methods: Wildtype and muscle-specific Drp1 heterozygote (mDrp1+/−) mice, as well as dysglycemic (DG) and healthy normoglycemic men (control) performed acute and chronic exercise. The Hybrid Mouse Diversity Panel, including 100 murine strains of recombinant inbred mice, was used to identify muscle Dnm1L (encodes Drp1)-gene relationships. Results: Endurance exercise impacted all aspects of the mitochondrial life cycle, i.e. fission-fusion, biogenesis, and mitophagy. Dnm1L gene expression and Drp1Ser616 phosphorylation were markedly increased by acute exercise and declined to baseline during post-exercise recovery. Dnm1L expression was strongly associated with transcripts known to regulate mitochondrial metabolism and adaptations to exercise. Exercise increased the expression of DNM1L in skeletal muscle of healthy control and DG subjects, despite a 15% ↓(P = 0.01) in muscle DNM1L expression in DG at baseline. To interrogate the role of Dnm1L further, we exercise trained male mDrp1+/− mice and found that Drp1 deficiency reduced muscle endurance and running performance, and altered muscle adaptations in response to exercise training. Conclusion: Our findings highlight the importance of mitochondrial dynamics, specifically Drp1 signaling, in the regulation of exercise performance and adaptations to endurance exercise training. Keywords: Mitochondrial dynamics, Drp1, Exercise performance, Exercise training